Enhanced Hole‐Carrier Selectivity in Wide Bandgap Halide Perovskite Photovoltaic Devices for Indoor Internet of Things Applications. (16th February 2021) - Lee, Minwoo; Choi, Eunyoung; Soufiani, Arman Mahboubi; Lim, Jihoo; Kim, Moonyong; Chen, Daniel; Green, Martin Andrew; Seidel, Jan; Lim, Sean; Kim, Jincheol; Dai, Xinchen; Lee‐Chin, Robert; et al.
Abstract: Halide perovskite‐based photovoltaic (PV) devices have recently emerged for low energy consumption electronic devices such as Internet of Things (IoT). In this work, an effective strategy to form a hole‐selective layer using phenethylammonium iodide (PEAI) salt is presented that demonstrates unprecedently high open‐circuit voltage of 0.9 V with 18 µW cm −2 under 200 lux (cool white light‐emitting diodes). An appropriate post‐deposited amount of PEAI (2 mg) strongly interacts with the perovskite surface forming a conformal coating of PEAI on the perovskite film surface, which improves the crystallinity and absorption of the film. Here, Kelvin probe force microscopy results indicate the diminished potential difference across the grain boundaries and grain interiors after the PEAI deposition, constructing an electrically and chemically homogeneous surface. Also, the surface becomes more p‐type with a downshift of a valence band maximum, confirmed by ultraviolet photoelectron spectroscopy measurement, facilitating the transport of holes to the hole transport layer (HTL). The hole‐selective layer‐deposited devices exhibit reduced hysteresis in light current density–voltage curves and maintain steadily high fill factor across the different light intensities (200–1000 lux). This work highlights the importance of the HTL/perovskite interface that prepares the indoor halide perovskite PV devices for powering IoT device. Abstract : The effect of phenethylammonium iodide (PEAI) deposition is investigated for indoor perovskite solar cells (PSCs). With an optimized amount of PEAI, homogenous extraction of photo‐generated carriers is observed. In addition, work function shifts toward the valence band of the surface. This results in enhanced hole collection between the hole transport layer and perovskite interfaces leading to improved performance of indoor PSCs.